H ∞ controller design for the mitigation of atmospheric effects on the laser beam pointing - Subasi, Ozgenc; Erol, Bilal; Altiner, Berk; Turan, Harun; Baci, Nurdan (SAGE PUBLICATIONS LTD, 2021)
In this paper, the control of a fast steering mirror, which is the core element of an adaptive optics system, is investigated to suppress the beam jitter. The main source of the jitter is taken as the atmospheric turbulence. The effect of the atmospheric turbulence on the beam jitter is experimentally determined with respect to the two different refractive index structure parameters. The mathematical model of the fast steering mirror based on the atmoshperic turbulence data is obtained using the system identification. In order to overcome implementation problems, the low order proportional-integral-derivative (PID) type controllers, which minimize the H infinity norm of the closed loop system, are designed in the centralized and the decentralized settings. In addition to this, the fixed order weighted H infinity controller is based on the frequency characteristics of the atmospheric turbulence that is determined experimentally. Then, in order to show the effectiveness of the proposed low order PID type controller, the designed controllers are compared on the experimental setup. Finally, the simulation and the experimental results are presented. Comparison of advantageous and disadvantageous of centralized and decentralized controller architectures are discussed.
Keywords: Adaptive optics; fast steering mirror; jitter control; H∞ control; PID; ADAPTIVE-CONTROL; OPTICAL JITTER; SIMULATION; TURBULENCE; Automation & Control Systems; Instruments & Instrumentation